The Effect of Self Efficacy, Job Description, and Organizational Climate on Productivity Employees at PT. Multi Terminal Petikemas Belawan - Gowasa, Yoiron; Pohan, Yuli Arnida (CV. Civiliza Publishing, 2025)
Study This aim For analyze influence self efficacy , job description , and climate organization to productivity Work employees at PT. Pelindo Multi Terminal Petikemas both partially and simultaneously. The method used in this study is a quantitative method with a multiple linear regression approach. Data were obtained by distributing questionnaires to employees and analyzed using a statistical program. The results of the study indicate that partially, the self-efficacy variable has a positive and significant effect on work productivity. This indicates that the higher the level of employee confidence and belief in their abilities, the higher their work productivity. Likewise, the job description variable, which is also partially proven to have a positive and significant effect on work productivity. Clarity of job descriptions has been shown to increase employee focus, effectiveness, and work efficiency. Meanwhile, the organizational climate variable, partially does not have a positive and significant effect on work productivity. This indicates that the existing organizational climate is not strong enough or conducive to encouraging increased individual productivity. However, when the three variables are tested simultaneously, namely self-efficacy, job description , and organizational climate, the results show a positive and significant effect together on employee work productivity. This finding indicates that work productivity is influenced by a combination of interacting internal and external factors. Therefore, company management needs to manage these three factors in an integrated and sustainable manner to create synergy that can improve overall employee performance.